Broad rim lesions are a new pathological and imaging biomarker for rapid disease progression in multiple sclerosis - Klotz, Luisa; Smolders, Joost; Lehto, Jussi; Matilainen, Markus; Lütje, Lukas; Buchholz, Luzia; Albrecht, Stefanie; Walter, Carolin; Varghese, Julian; Wiendl, Heinz; Nylund, Marjo; Thomas, Christian; et al. (Springer Nature, 2025)
Current multiple sclerosis (MS) treatments reduce relapse activity but have limited impact on disease progression. Clinical trials targeting progression often fail because of insufficient understanding of its underlying mechanisms. This study analyzed a clinically well-characterized MS autopsy cohort from the Netherland Brain Bank (186 individuals) from which we selected donors exhibiting opposite disease trajectories of slow versus rapid progression. We performed extensive unbiased histology and spatial transcriptomics, which unveiled a distinct MS lesion type marked by an extensive myeloid cell rim with cellular and transcriptional signatures of innate immune activation, inflammatory cytokine production, unfolded protein response and apoptosis. Presence of this particular lesion type was linked to rapid disease progression. An independent translocator protein 18-kDa positron emission tomography study (114 individuals) validates the association between lesions with a broad myeloid cell rim and disease progression in individuals with MS. Our findings offer crucial insights into the mechanisms behind MS progression, identifying broad rim lesions as a biomarker for rapid disease progression and potentially guiding patient selection for future therapeutic trials targeting central nervous system intrinsic inflammation.